PKM permainan tradisional bagi guru sekolah dasar di Kabupaten Takalar - Andi Atssam Mappanyukki; Abdul Rahman (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Traditional games as one among the peoples ' cultural elements are scattered in various Pencuru archipelago, but nowadays its existence has gradually experienced. Especially for those who currently live in the urban, even some of them can not be recognized by the community in which the game exists. This game provides relaxing effect after a day of children doing activities both in school and at home, in other words able to overcome the saturation of the child. According to Moritz Lazarus, the child played because they needed a refresher or a return of energy used for routine daily activities. This means that playing is a relaxation and recration activity that makes children feel refreshed. (Tadkiroatun Musfiroh, 2005). The methods used in this activity are lectures and questioning and field practice conducted for three days. This activity is very beneficial for students and Gurur because it is able to give a sense of comfort and relax to participants. The participants realized that this activity was able to provide additional knowledge about traditional games. The advice given with this activity, conducting socialization and similar training in other students and schools in other sub-districts. There is a connection to this community partnership program so that students and teachers can actually practice traditional game skills.